Humidity effect on electrical properties of graphene oxide back-to-back Schottky diode - Shaharin Fadzli Abd Rahman; Nurul Anati Salleh; Mastura Shafinaz Zainal Abidin; Amirjan Nawabjan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A Schottky diode-based sensor is a promising structure for high sensitive and low power sensor. This paper investigates a device called back-to-back Schottky diode (BBSD) for humidity sensing operation. The BBSD provides simpler device configuration that can be fabricated using less complicated process. The current-voltage characteristic of the fabricated BBSD was measured at different relative humidity. From the obtained characteristics, series resistance, barrier height and ideality factor was analyzed. The device current increased at higher humidity level. The current increase could be associated to the decrease in series resistance, barrier height and ideality factor. When humidity decreased from 11 % to 97%, the barrier height showed reduction of 0.1 eV. The barrier height reduction was explained by considering electric field-induced reduction of graphene oxide. The observed result confirmed the device feasibility as promising simple and low cost humidity sensor.